Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Pecahan Ditinjau Dari Pemecahan Masalah Polya (Kelas VII SMP Negeri 23 Surakarta Tahun 2016/2017) - Aji Nugroho, Reza; , Dra. Sri Sutarni, M.Pd (2017)
ABSTRACT story on the material fractions. This study used a qualitative descriptive. Data collection techniques by observation, tests and interviews. Data validity checking with the technique of triangulation method, by comparing the results of tests, interviews, and observations. Analysis of the data through the stages of data reduction, data presentation and conclusion. Pursuant to data analysis and discussion of students experiencing errors are: 1. Understanding the problem, the error in defining the language and create mathematical models. The cause is the reasoning Incomplete / incorrect and the ability of students is low. 2. Planning for problem solving that is an error connecting one concept with another concept .. The cause of this error is a humanistic thinking students. 3. Carry out planning problem solving, which is a mistake to implement a formula that is not appropriate. Errors on this aspect due to the reasoning (reasoning) is incomplete or incorrect and humanistic thoughts of students. Keywords: error, fractions, word problems